Pollination in the tropics: role of pollinator in guava production - Omar, Nurul Alia; Zariman, Nur Athirah; Abdul, Nurul Huda (International Society of Academicians, 2021)
Pollinators are the key point for successful pollination in most flowering plants where around 90% of plants depend entirely on them. Majority of the pollinating species are wild, comprising bees, certain species of flies, wasps, moths, butterflies, thrips, beetles, bats, birds and other vertebrates, and among them insect pollinators are the most crucial. Fruit crops benefit in an impressive way from insect pollination, where there is a remarkable improvement both in the productivity and the quality of self-fertilized, self- incompatible and cross-cropping crops worldwide. The pollinators are responsible for assisting these flowering plants with their reproduction. However, the crisis of the pollinator’s decline (wild and managed pollinators) which could seriously disrupt pollination activities in the ecosystems has attracted the attention of the world. Despite the growing concern about the decline in pollinators worldwide, some issues remain uncertain as data are often limited and undermined. Guava, Psidium guajava is a marketable fruit in numerous tropical and subtropical regions around the world. There has been a growing interest in pollination studies on guava because of its great economic importance. In guava, self-pollination is evident, however, it benefits greatly from insect pollination. This article aims to provide an overview of tropical pollination and pollination problems that have occurred around the world with a focus on pollination activities in guava.